Strigolactones regulate sepal senescence in Arabidopsis. (10th May 2021) - Xu, Xi; Jibran, Rubina; Wang, Yanting; Dong, Lemeng; Flokova, Kristyna; Esfandiari, Azadeh; McLachlan, Andrew R G; Heiser, Axel; Sutherland-Smith, Andrew J; Brummell, David A; Bouwmeester, Harro J; Dijkwel, Paul P; et al.
Abstract : Two novel mutants in the strigolactone pathway demonstrate a role for the hormone in sepal senescence, and transcriptional analysis highlights interaction between strigolactones and sugar signalling. Abstract: Flower sepals are critical for flower development and vary greatly in life span depending on their function post-pollination. Very little is known about what controls sepal longevity. Using a sepal senescence mutant screen, we identified two Arabidopsis mutants with delayed senescence directly connecting strigolactones with senescence regulation in a novel floral context that hitherto has not been explored. The mutations were in the strigolactone biosynthetic gene MORE AXILLARY GROWTH1 ( MAX1 ) and in the strigolactone receptor gene DWARF14 ( AtD14 ). The mutation in AtD14 changed the catalytic Ser97 to Phe in the enzyme active site, which is the first mutation of its kind in planta . The lesion in MAX1 was in the haem–iron ligand signature of the cytochrome P450 protein, converting the highly conserved Gly469 to Arg, which was shown in a transient expression assay to substantially inhibit the activity of MAX1. The two mutations highlighted the importance of strigolactone activity for driving to completion senescence initiated both developmentally and in response to carbon-limiting stress, as has been found for the more well-known senescence-associated regulators ethylene and abscisic acid. Analysis of transcript abundance in excised inflorescences during an extended night suggested an intricate relationship among sugar starvation, senescence, and strigolactone biosynthesis and signalling.